Adolf Szyszko-Bohusz Warszawianka Building in Zegiestow - Tomas Sliwinski (Docomomo Journal, 2022)
When Poland recovered its freedom after World War I, the concept of modernism, as in all of central Europe, became increasingly popular. Modern architecture, inspired by Poland's rapid progress and changes in the sciences and industry, was built in the main cities such as Krakow and Warsaw as well as in rural regions. This trend was popularized by neww public and military constructions such as Gdynia's harbor buildings. lncrea!singly, architects adopted the design principles of modern architecture and started to reject the prevalent decorative style of the previous decades.